SEBUAH KAJIAN KEBAHASAAN - Zulisih Maryani (Rekam: Jurnal Fotografi, Televisi, Animasi)
The purpose of this study is to describe (1) the time of show of televisionslogan, (2) the language aspects which forming the television slogan, (3) the meaning of the slogans belong to the television station, (4) the persuasion techniques used in television slogan, (5) the influence of slogan ownerships to their television stations, and (6) to describe the differences between the specifications of local television slogans and national television slogans. Television slogan had been shown in every lag time or between the television programs. Television slogans have certain meanings in accordance with the vision, mission and the types of programs presented in a television station. To make the television slogans some linguistics aspects are applied, such as the use of sound, foreign language, and figure of speech. The persuasion techniques used in the creation of television slogan is then rationalized and identified. Having television slogans is one of the trademarks or identities of a television station, as far as it does not give a significant influence on some television stations that do not have slogans, for example in the number of the viewers. The different specifications of local television slogans and those of national television is that if in the slogan of local television they still apply local dialect or certain vocabulary from the native culture, the national television slogan apply national language or Indonesian language.Keywords: television slogans, meaning, language aspects, persuasion techniques